Effects of a nitrogen seeded plasma on nanostructured tungsten films having fusion-relevant features. (December 2020) - Uccello, Andrea; Ghezzi, Francesco; Laguardia, Laura; Caniello, Roberto; Dellasega, David; dell'Era, Fabio; Della Torre, Davide; Donnini, Riccardo; Granucci, Gustavo; Mesto, Ernesto; Minelli, Daniele; Passoni, Matteo; et al.
Abstract: Nitrogen (N) seeding is routinely applied in tokamaks with tungsten (W) walls to control the power exhaust toward the divertor. Open questions, concerning the interaction of N with W, are the influence of ion energy and W temperature on retention of implanted N and the erosion by deuterium (D) of the tungsten nitride being formed. Moreover, the extremely high particle fluxes in ITER and DEMO will erode the W tiles and the sputtered atoms will re-deposit forming W-based layers with a different behaviour toward the interaction with N seeded D plasmas. In this work, W films with different morphology and structure were exposed to the N seeded D plasma of the linear device GyM, in order to address all these issues. The experiments were performed at the fixed N 2 /D 2 partial pressure ratio of ∼ 4% keeping the total pressure constant at 5.3 × 1 0 − 4 mbar. The exposure conditions were: (i) sample temperature of ∼ 850 K, (ii) particle fluxes of 2 − 2 . 2 × 1 0 20 ions ⋅ m − 2 ⋅ s −1 and (iii) particle energies up to ∼ 320 eV. W columnar films (c-W) with properties close to those of virgin W coatings deposited on the tiles of JET Iter-Like Wall and ASDEX Upgrade and W amorphous films (a-W) resembling nanostructured W-based deposits found in present-day tokamaks and expected in ITER and DEMO, were considered. W columnar and amorphous coatings were produced by means of magnetron sputtering and pulsed laser deposition, respectively. The specimens were characterised by profilometry, X-ray depth-profiling photoelectron spectroscopy, optical microscopy, scanning electron microscopy, atomic force microscopy and X-ray diffraction. The main evidence is that the behaviour of the W films upon D+N plasma exposure in GyM strictly depends on their morphology and nanostructure. For all the films, a surface N-enriched layer, which is thermally stable and does not decompose at least up to ∼ 850 K, is observed. Moreover, blisters are not present on the surface of the samples. The c-W coatings erode faster than the a-W ones and have a higher nitrogen retention and diffusivity. The mechanisms behind these results are here discussed together with their possible implications from the point of view of the topic of plasma–wall interaction in tokamaks. Highlights: Fusion-relevant W films were exposed to N seeded D plasma in the linear device GyM. Exposures were carried out at 850 K and plasma ions impinging energy up to 320 eV. For all films, a surface N-enriched layer, thermally stable up to 850 K, was observed. All films were free of blisters after the exposures. Erosion and nitrogen retention depend on W films morphology and nanostructure.